2017
DOI: 10.1371/currents.dis.07059b54a787dcfcf53ac46ab5a6a809
|View full text |Cite
|
Sign up to set email alerts
|

In the Field Feasibility of a Simple Method to Check for Radioactivity in Commodities and in the Environment

Abstract: Introduction:Some release of radionuclides into the environment can be expected from the growing number of nuclear plants, either in or out of service. The citizen and the big organization could be both interested in simple and innovative methods for checking the radiological safety of their environment and of commodities, starting from foods.Methods:In this work three methods to detect radioactivity are briefly compared  focusing on the most recent, which converts a smartphone into a radiation counter.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It concludes from this research that Radioactivity Counter can measured radiation without any additional hardware at the dose rates higher than 10 μGy/h [23]. The relation between cpm and dose rate was confirmed to be linear due to previous research [20], [21], [23]. Previous iPhone model (4, 4s, 6), iPod, iPad and various android based smartphone models have been tested in previous research [19]- [25].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…It concludes from this research that Radioactivity Counter can measured radiation without any additional hardware at the dose rates higher than 10 μGy/h [23]. The relation between cpm and dose rate was confirmed to be linear due to previous research [20], [21], [23]. Previous iPhone model (4, 4s, 6), iPod, iPad and various android based smartphone models have been tested in previous research [19]- [25].…”
Section: Introductionsupporting
confidence: 58%
“…The finding was the counts (cps) were linear to the dose rate (mSv/hr) [20]. Alessandri (2017) in his research of finding the simple method of radioactivity detection in commodities and environment using smartphone-based application to check radioactivity. The finding was smartphone was able to detect radiation in certain condition such as emergency [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other smartphones exhibit different CMOS sensitivity for different systems of the same type 12 . Alessandri 18 assessed the use of three smartphones (Samsung S4, Samsung S7, and Samsung A3) for radiation detection with different radiation sources (Na-22, Zn-65, and Cs-137). The study reported that the smartphones responded contrarily to radiation.…”
Section: Resultsmentioning
confidence: 99%